PENDIDIKAN ISLAM DI PESANTREN : Telaah Pendidikan Islam di Pesantren dari Masa Kolonial – Modern - Fahmi Khumaini; Ainun Hakiemah (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2021)
Pesantren has long been known as an Islamic institution in Indonesia has a significant role in the intellectual life of the nation, in the world of education, especially in Islamic education. During the colonial period, pesantren was highly hostile and suspected by the colonizers, moreover, the pattern and education system contained in the pesantren had its uniqueness which always faced vis a vis the secular education brought by the colonizers. After Indonesia's independence, pesantren were often suspected of having anti-Indonesian government attitudes. Pesantren at the beginning of its development, apart from being a tafaqquh fiddin institution, whose function was to broadcast religion by providing a place for religious learning, a social institution that taught various things about mental education and its maintenance. The approach in this study is literature with a literature review, the results of the study found that Islamic boarding schools experienced changes and developments from time to time, there were shifts in values, structures, views in every aspect of pesantren, including changes in aspects related to the world of education and teaching that more modern.